(untitled) (Alternautas, 2022)
We are happy to share with our readers a series of seven articles, to be published between mid-October and mid-December, from diverse disciplinary perspectives – including anthropology, archaeology, political science, development studies and critical sociology and geography – showing the diversity of existing approaches to study water (neo)extractivism. Moreover, the special issue covers a large geographic area, with two cases from Central America – Honduras and Guatemala – and five cases from South American countries – Chile, Peru, Bolivia, Brazil and Colombia.